Biaxial Shear Load Capacity of Anchor System for Quick-Hardening Track on Railway Bridges - Kyoung Chan Lee; Il-Wha Lee; Seong-Cheol Lee (Advances in Civil Engineering)
Quick-hardening railway track was developed to rapidly convert old-style ballast track to slab track in order to improve its maintainability and ride comfort. On bridges, quick-hardening track is applied in a segmented structure to reduce the temperature constraint, and anchors at the centers of the segments securely couple the track to the bridge. In this study, an anchor system is proposed that facilitates fast construction, and two designs for the proposed anchor systems are provided along with experimental test results of the same. Two anchor system designs were developed to allow for the maximum possible longitudinal and transverse loads in high-speed railways while considering the frictional resistance between the track slab and bridge deck. The biaxial shear capacity of each design was investigated experimentally, and the structural capacity for biaxial shear loads was evaluated using an elliptical curve to represent the longitudinal and transverse shear capacities. The minimum friction coefficient was determined based on the results of the evaluation to minimize damage to the anchor. The results obtained from the experiments confirmed that the proposed anchor systems possess sufficient shear capacity for application on high-speed railway bridges.